Über die Bereiche der gleichmässigen Konvergenz der Newtonschen Reihe und der Fakultatenreihe - Morosjuk, E. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Э. В. Морозюк. Об областях равномерной сходимости рядов Ньютона и факториальногоE. Moroziuk. Niutono ir faktorialinių eilučių tolygios konvergencijos sritys